Digital Literacy sebagai Prediktor Knowledge Sharing Intention pada Sektor Industri di Indonesia - Agung, Hironimus; Pribadi, Yoke; Caroline, Angela; Gunawan, Agus (Jurnal EMT KITA, 2025)
This study aims to analyze the influence of digital literacy on knowledge sharing intention among employees across various industrial sectors in Indonesia, as well as explore the relationship between demographic characteristics and knowledge sharing intention. The research employed a mixed-method approach with a quantitative method dominance. The research sample consisted of 123 respondents working in various industrial sectors. The results showed that digital literacy has a significant and positive influence on knowledge sharing intention. Cross-tabulation analysis revealed that education level, work sector, and domicile have significant relationships with knowledge sharing intention, while gender shows no significant relationship. These findings provide important implications for organizations in designing digital competency development programs and effective knowledge management strategies.